Study on effect of crushed tile as coarse aggreagate replacement in concrete - Fauzurrahman, Zulkepli (2012)
As a developing country, more and more old buildings tom down to be replaced by new buildings in line with current technological advances. At the same time, construction and demolition (C&D) waste will also increase. Therefore, rather than allow the C&D waste without the benefit, it is also can be used as coarse aggregate in concrete. C&D waste which is include concrete rubble, tile and waste bricks can be use as alternative material for concrete mix. This research is discussed about using crushed tile which is one of C&D waste as coarse aggregate in concrete mixing. The performances in term of engineering properties of concrete using crushed tile as coarse aggregate replacement were investigated. There are four series of concrete mix design with 0%, 5%, 10% and 15% were designated as Sample A, B, C and D. 36 number of cube sample with dimension of 150 mm x 150 mm x 150 mm and 12 number percentage cylinder sample with diameter 150 mm and height 300 mm were produced. The result of this research can be identified after laboratory testing such as workability test, compression test and splitting tensile test. Result of workability test shows that all tests are high in workability category. It was found that at age 28 days the compressive strength values for sample B is increased 4.08% than sample A. Splitting strength results were similar and higher compare to control sample.